(untitled) (Medico Legal Update, 2020)
Background/Objectives: This study is an experimental study to investigate the effect of Dialectical Behavior Therapy (DBT) skills training on depression and abstinence self-efficacy of people with alcohol use disorder.. Methods/Statistical analysis: The study was conducted on patients with alcohol use disorder diagnosed in one mental health department hospital, and 10 subjects were included in the control group receiving medication and 10 subjects were in the experimental group receiving additional dialectical behavior therapy skills training. Data collection was conducted from July 17, 2017 to September 4, 2017, once a week for a total of 8 sessions. The collected data were analyzed by Mann-Whitney U test, Friedman and repeated measure ANOVA. Findings: The results showed that there was a significant effect on the viewpoint and interaction of the experimental group and the control group on depression, and the abstinence self-efficacy showed a significant difference in the pre-post-follow up period. Improvements/Applications: It is expected that this program will continue to be used in education for the treatment and rehabilitation of patients with alcohol use disorders.